SIGNIFICANCE OF MARKERS IN INFLAMMATORY AND CONNECTIVE TISSUE AT TEMPOROMANDIBULAR JOINT DISEASESIN CHILDREN - Saidov, A.A.; Gafforov, S.A; Olimov, S.Sh. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To study features of some connective tissue markers in development of TMJ pathology at children. Materials and methods: Research has been based on medical examination results of 65 children in aged 6 to 15 years with TMJ pathology. Patients’ examination was carried out according to scheme, including clinical methods, morphometric methods, biometric study, x-ray methods, dental computed tomography and serum C-RP concentration which was determined by enzyme-linked immunoassay. Results: systemic metabolism of connective tissue at patients with dysplasia is characterized by release of glycoproteins, a decrease in sulfated glycosaminoglycan. Beyond, they also is determined rheological properties of blood, which serves as an explanation for occurrence of typical disorders of hemostasis in DAA, affecting thrombophilia caused by systemic inflammatory response, which explained predominance of degradation of glycosaminoglycan on their synthesis. Conclusions: as a result of the obtained data, it was revealed that at children with temporomandibular joint disease were a significant increase in glycosoaminglican level in serum when compared with a group of healthy children.